Prevalence and sociodemographic correlates of cervicovaginal human papillomavirus (HPV) carriage in a cross-sectional, multiethnic, community-based female Asian population. (27th November 2017) - Khoo, Su Pei; Bhoo-Pathy, Nirmala; Yap, Siew Hwei; Anwar Shafii, Mohd Khairul; Hairizan Nasir, Nazrilla; Belinson, Jerome; Subramaniam, ShriDevi; Goh, Pik Pin; Zeng, Ming; Tan, Hong Dong; Gravitt, Patti; Woo, Yin Ling
Abstract : Objectives: Cervical cancer is a largely preventable disease, and the strategic implementation of a cervical cancer prevention programme is partly dependent on the impact of human papillomavirus (HPV) infection interpreted within the context of the country's sociodemographic attributes. The objective of this study is to determine the prevalence of cervicovaginal HPV infection among a healthy, community-based, multiethnic Malaysian population. The HPV prevalence was subsequently correlated to the individual's sociodemographics and sexual/reproductive history. Of significance, the observed prevalence captured was in a birth cohort not included in the national school-based HPV vaccination programme. Methods: This was a cross-sectional study where 1293 healthy women aged between 18 and 60 years were recruited via convenience sampling from five community-based clinics in Selangor, Malaysia. Cervicovaginal self-samples were obtained and DNA was extracted for HPV detection and genotyping. A comprehensive questionnaire was administered to determine the sociodemographics and behavioural patterns of participants. Results: The median age at enrolment was 37 years old (IQR: 30–47). In total, 86/1190 (7.2%) of the samples collected were positive for HPV infection, with the highest HPV prevalence (11.9%) detected in the subgroup of 18–24 years old. The top three most prevalent HPV genotypes were HPV 16, 52 and 58. The independent risk factors associated with higher rates of HPV infection included Indian ethnicity, widowed status and women with partners who are away from home for long periods and/or has another sexual partner. Conclusions: The overall prevalence of HPV infection in this Malaysian multiethnic population was 7.2%, with 6.5% being high-risk genotypes. The top three most common high-risk HPV types were HPV 16, 52 and 58. This information is important for the planning of primary (HPV vaccination) and secondary (screening) cervical cancer prevention programmes in Malaysia.